3D graphic laser safety notification system for industrial human-robot cell - Seet, Gerald Gim Lee (2021)
Human and robot need to interact to perform complex tasks through mutual understanding. There are generally no effective means of communication from robot-to-human to express its ‘intention’. Effective recognition of a robot’s intention can mitigate potential conflicts or accidents. This is particularly important in the context of factories of the future where human and robot are expected to work in a shared environment. Beyond the relative structure of a factory, autonomous vehicles operate in shared environments with pedestrians and the ability of humans and autonomous vehicles to understand the other’s intention is crucial. In most environments, audio notifications, lack in effectiveness. The environment may be noisy and there is an additional problem of language and its understanding. Visual display may provide a better alternative. The use of traditional image projectors, for this purpose, has severe limitations in bright surroundings. Image brightness is crucial, and traditional video projection are typically confined to indoor usage or in the evening when the surrounding is relatively dark. In contrast, laser projection is seldom short of brightness, but there is a limit to the speed of vector drawing and power of commercially available laser projectors allowed for use in public space.